2014
DOI: 10.2989/16085906.2014.892015
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider perspectives on improving the linkage of HIV-positive pregnant women to long-term HIV care and treatment in eastern Uganda

Abstract: Despite strong evidence that antiretroviral therapy (ART) reduces the risk of mother-to-child transmission of HIV and improves the health of HIV-positive mothers, many HIV-positive pregnant women do not enrol into long-term HIV care and treatment. This study examined barriers and facilitators to the linkage of HIV-positive pregnant women from antenatal care (ANC) to long-term HIV care from patient and provider perspectives, following the implementation of a collaborative quality improvement project in Eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Many studies and reviews have assessed the effectiveness of the integration of HIV and SRH services, discussing issues around coverage, service uptake and time-to-treatment initiation [714], access to quality services [15], providers’ experiences and willingness to deliver joint services [1623], cost-effectiveness [24, 25], and health systems barriers to integration [2, 3, 26, 27]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies and reviews have assessed the effectiveness of the integration of HIV and SRH services, discussing issues around coverage, service uptake and time-to-treatment initiation [714], access to quality services [15], providers’ experiences and willingness to deliver joint services [1623], cost-effectiveness [24, 25], and health systems barriers to integration [2, 3, 26, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…Less information exists on patients’ experiences with integrated care, primarily among pregnant women [26, 34, 37]. A study on improving the linkage of HIV-positive pregnant women to long-term HIV care and treatment in eastern Uganda reports that facilitating factors for linked care include (among others) support from expert clients, escorted referrals, and coordination between ANC and HIV service; while reported barriers for women included shortages in HIV testing kits and fear of social, physical and medical consequences [26].…”
Section: Introductionmentioning
confidence: 99%
“…Women in two studies reported fear of physical violence from partners if they found out about their HIV status [24,41], while having adequate support from a partner or family member was reported as an enabler of transition [5,21]. Women transitioning from ANC to ART clinics to start treatment reported fear of medication side effects and the burden of being on treatment as additional barriers [22,24,41].…”
Section: Fearmentioning
confidence: 99%
“…Despite the need for strong linkages and collaborations between the multi-dimensional aspects of care, most programs have struggled to maintain linkage and cross-referral systems. 20,21…”
Section: Barriers To Testing and Care For Heimentioning
confidence: 99%